PAIN AND EMERGENCY DEPARTMENT USE IN THE LAST MONTH OF LIFE BY OLDER ADULTS WITH DEMENTIA. (11th November 2018) - Hunt, L; Ritchie, C; Patel, K; Stephens, C; Cataldo, J; Smith, A
Abstract: Although both pain and Emergency Department (ED) visit rates increase markedly for older adults at end-of-life, little is known about the relationship between pain and ED use at end-of-life among older adults dying with dementia. To examine the effect of pain and pain management on ED visit rates in decedents with dementia, we conducted a mortality follow-back study of fee-for-service Medicare decedents aged 65+ with dementia enrolled in the National Health and Aging Trends (NHATS) between 2011 and 2014. NHATS data was linked to Medicare claims and Poisson regression was used to model the relationship between pain and ED visits, adjusting for age, gender, and race. 291 NHATS participants with dementia met criteria (mean age 86, 60% female, 80% white). 56% had at least one ED visit in the last month of life. According to post-death interviews with proxy respondents, 73% of decedents experienced pain in the last month of life, and 10% had poorly managed pain. In adjusted models, the presence of pain was not associated with increased ED use (Adjusted Incident Rate Ratio (aIRR 0.87, 95% CI 0.66–1.14). However, decedents with poorly managed pain had a 50% higher rate of ED visits in the last month of life compared to those with well-managed pain (aIRR 1.51, 95% CI 1.10–2.07). In conclusion, among older adults with dementia, poorly managed pain may be associated with more frequent ED visits in the last month of life. ED visit rates could be reduced with interventions to improve pain management in this group.